Parent and health professional perspectives in the management of adolescents with diabetes: development of assessment instruments for international studies - Hoey, Hilary; McGee, Hannah M; Fitzgerald, Michael; Mortensen, Henrik B; Hougaard, Philip; Lynggaard, Helle; Skovlund, Soren E; Aanstoot, Henk-Jan; Chiarelli, Francesco; Daneman, Denis; Danne, Thomas; Dorchy, Harry; et al. (Springer, 2006)
Objective: Assessment of quality of life (QOL) in adolescents with diabetes requires patient, parent and health professional input. Psychometrically robust instruments to assess parent and professional perspectives are required. Research design and methods: Questionnaires concerning adolescent QOL were developed for completion by parents and health professionals. In an international study assessing QOL in 2,101 adolescents with diabetes (median age 14 years, range 10–18; from 17 countries including Europe, Japan and North America), parents and health professionals completed their respective questionnaires between March and August 1998. Results: Feasibility and acceptability of the new questionnaires were indicated by high questionnaire completion rates (adolescents 92%; parents 89%; health professionals 94%). Internal consistency was confirmed (Cronbach’s α coefficients 0.80 parent; 0.86 health professional). Correlations of Diabetes Quality of Life Questionnaire for Youths (DQOLY) scores with parent and health professional global QOL ratings were generally low (r ranging from 0.12 to 0.36). Parent-rated burden decreased incrementally across adolescence, particularly for girls. Professional-rated burden followed a similar profile but only after age 15 years. Until then, burden was rated as uniformly high. Clinically relevant discrepancies in parent and professional burden scores were noted for one-parent families and families where adolescents had been referred for psychological help. In both cases, health professionals but not one-parent families perceived these as high burden situations. The clinical significance of this relates to the significantly poorer metabolic control recorded for adolescents in both situations. Conclusions: Parent and health professional questionnaires were found to have adequate internal consistency, and convergent and discriminant validity in relation to key clinical and QOL outcomes. The questionnaires are brief, easy to administer and score. They may also enable comparisons across countries and languages to facilitate development of international health outcome parameters. The inclusion of the parent and health professional perspectives completes a comprehensive assessment of adolescent QOL relevant to diabetes.